2019
DOI: 10.25105/ber.v16i2.5088
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction, Hospital Image and Patient Loyalty in West Sulawesi Province

Abstract: The purpose of this study was to examine and analyze the effect of patient satisfaction and hospital image on patient loyalty. The research design uses a survey method with cross-section data collection through a questionnaire. As a sample in this study, 124 patients were hospitalized at a Private Hospital located in West Sulawesi Province and taken by simple random sampling. The data analysis method used in hypothesis testing is Structural Equation Modeling (SEM). The results of the study provide evidence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 51 publications
2
40
0
Order By: Relevance
“…The similarity of brand personality and the authenticity of brand extension (Sattayawaksakul et al, 2019). With technological development in recent years, consumers come to choose the products which can meet their brand demands, so a good brand image for an enterprise is the key to successful marketing (Ogba & Tan, 2009;Ramli, 2017). When consumers have brand awareness, the value of the brand makes consumers remain loyal to the products, and thus positively influencing the brand identity and increasing brand equity (Shabbir et al, 2017).…”
Section: The Impact Of Brand Loyalty On Brand Imagementioning
confidence: 99%
“…The similarity of brand personality and the authenticity of brand extension (Sattayawaksakul et al, 2019). With technological development in recent years, consumers come to choose the products which can meet their brand demands, so a good brand image for an enterprise is the key to successful marketing (Ogba & Tan, 2009;Ramli, 2017). When consumers have brand awareness, the value of the brand makes consumers remain loyal to the products, and thus positively influencing the brand identity and increasing brand equity (Shabbir et al, 2017).…”
Section: The Impact Of Brand Loyalty On Brand Imagementioning
confidence: 99%
“…Hospital service quality can lead to employee and patient satisfaction. It also results in building loyalty in patients toward hospitals and encourages them to recommend such healthcare centers to friends and those around [3,4]. Consideration of quality can thus reduce costs in organizations, increase e ciency, and provide long-term stability [5].…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced service quality and increased levels of satisfaction can ultimately boost customers' trust in organizations [3]. Trust can thus improve patients' mental well-being and peace of mind.…”
mentioning
confidence: 99%
“…According to the results of Surydana (2017) in Indonesia, health care services and patient satisfaction have a personalized value, significantly influencing customer satisfaction. Haeba (2017), also in Indonesia, analyzed the relationship between hospitalised patient satisfaction, hospital image and patient loyalty. The results obtained showed that high patient satisfaction has a positive impact on loyalty, and the same effect has an image of the hospital.…”
Section: Introductionmentioning
confidence: 99%